Analysis of Soil Enzymes During the Cyclic Process of Vineyard Management - Mundaganur, Dastigir Sayyad; Mundaganur, Yasmin Dastigir; K.V., Ashokan (International Journal of Applied Sciences and Biotechnology, 2016)
Keeping soil quality at par is one of the needed things for sustainable development and the existence of millions of living things in biosphere. Soil enzymes are used as soil quality indicators for quick response of changes for environmental stress, pollution and agricultural practices much more sooner (1–2 year) than other soil properties (organic matter); easy to measure (relatively simple procedure), having relations with plant productivity, soil quality parameters (organic matter, soil physical properties, microbial activity, and microbial biomass), and biogeochemical cycle; and being integrative. To assess the detrimental effect of the soil in grape cultivating field we selected four farming sites and various soil enzymes like protease. Urease, cellulose, chitinase, beta glocosidase, phosphatase, amylase, aryl sulphatase and dehydrogenase. As an additional support, we estimated the microbial population in all these fields and in all the stages of the cyclic process of the vine cultivation. Our study showed that the extensive use of the chemical pesticide badly affect the soil microorganism and which in turn badly affect the quality and quantity of the soil enzymes and subsequently the quality of the soil. Int J Appl Sci Biotechnol, Vol 4(1): 67-73